Collision Tumor of the Ovary. Adjunction Cystic Teratoma and Serous Cystic Adenofi broma. Presentation of a Rare Case - Sofoudis C; Louis K; Papamargaritis E; Lenos M; Gerolymatos A (Journal of Surgery and Surgical Research - Peertechz Publications, 2018)
Ovarian cystic teratomas consist of germ cell tumors. They appear in female patients aged 20-40 years, comprising 15% of all ovarian neoplasms. These tumors appear in 90% of cases unilateral. Benign serous cyst-adenofi bromas represent the most common ovarian epithelial tumor, with an incidence of 42%, accounting 83% of serous ovarian tumors. The mean diameter estimates among 5 and 35 cm, with a bilateral incidence of 35%. A collision tumor is composed of two adjacent, histological distinct neoplasms without the histological intermixture of cell types in the same organ or tissue. According to current bibliography, these tumor types can be depicted in various organs including esophagus, stomach, liver, lung, thyroid, and kidney and of course ovary. There are few reported cases describing the ovarian type. The objective of our study refl ects the depiction of a rare collision ovarian tumor properly diagnosed and treated. The therapeutic mapping is strongly accompanied with the age and the fertility preservation of the patient.